Smart Hospitality: Key Drivers of Digital Technology Usage of Hotels in Cauayan City, Isabela, Philippines - Rojohn Mark P.Ramiscal; Mark Joseph Martinez; Jayson Pallaya; Rafael Villasana; Albert S. Alejandro; Client William M. Malinao (Pondok pesantren As-salafiyah As-Safi'iyyah, 2026)
In an era where digital innovation reshapes the hospitality industry, hotels’ ability to adopt and integrate smart technologies has become a critical determinant of competitiveness and service excellence. Thus, this study investigated the key factors influencing digital technology adoption among hotels in Cauayan City, Isabela, Philippines- an emerging tourism hub. Specifically, it aimed to (1) identify drivers affecting digital technology usage, (2) determine the level of usage of digital technologies, and (3) examine the relationships between these factors and actual technology usage. A descriptive–correlational design was employed, collecting data from 135 hotel managers and staff via a validated and reliable survey instrument (Cronbach’s α = 0.91). Using frequency and percentage distribution, weighted means, Pearson-r correlation, findings revealed that financial resources availability (M = 3.92) emerged as the most influential factor, followed by insights (M = 3.75), culture (M = 3.69), technology (M = 3.68), organization (M = 3.64), and government regulations (M = 3.54) as perceived by the respondents. Hotels demonstrated strong adoption of e-payments, smart room key systems, and mobile check-in/out, though no use of artificial intelligence, robotics and virtual reality highlighted opportunities for advanced digital integration. Correlation analysis confirmed moderate to strong positive relationships between determinants and technology usage, with organizational (r = 0.540, p = 0.001) and technological (r = 0.537, p = 0.001) factors as the strongest predictors. Cultural, insight, financial, and regulatory factors also showed significant associations. Findings suggest that hotels with strong leadership, adequate resources, technological readiness, and a culture of innovation are more likely to achieve sustainable digital transformation. The study extends the Technology–Organization–Environment and Technology Adoption Model framework to a local hospitality context and provides actionable insights for hotel managers and policymakers seeking to foster smart, data-driven, and competitive hotel operations. Keywords: digital technology adoption; smart hospitality; hotel management; Cauayan City, Isabela, Philippines